KEWENANGAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM PENEGAKAN HUKUM E-TLE BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009: Indonesian State Police Authority Regarding E-TLE Law Enforcement based on Law Number 22 of 2009 - Fiqih Haiqal; Ferry Edwar (Reformasi Hukum Trisakti, 2025)
Traffic infractions are among the most prevalent and readily identifiable breaches of the law. The rising incidence of road accidents illustrates this tendency. Law Number 22 of 2009 concerning Traffic and Road Transportation contains regulations pertaining to traffic and road transportation. Enhancing services in the areas of comfort, safety, security, and efficient traffic is the aim of the Traffic and Road Transportation Law. In this study, the problems found were whether they were in accordance with the provisions in Law No. 22 of 2009 concerning Traffic and Road Transportation with the authority of the Police in implementing the Electronic Traffic Law Enforcement (E-TLE) system to the Community and what were the legal obstacles in the implementation of Electronic Traffic Law Enforcement (E-TLE) at the West Jakarta Police Resort (Polres) in 2022. The research methodology used is a descriptive analytical normative legal research approach using qualitative analysis. The results and conclusions show that West Jakarta Police have carried out their duties and authorities in implementing E-TLE in accordance with Law Number 22 of 2009 concerning Traffic and Road Transportation and obstacles experienced are that community has not yet evenly socialized E-TLE policy system so that a review will be carried out.